National Agricultural Market in India: long way to solve the agri-marketing conundrum - Kumar, Ranjit; Kumar, Sanjiv; Meena, P. C. (Indian Farming, 2018)
For the National Agriculture Market dream to realize on ground, the interest of all the stakeholders must be taken care of. Be it the farmer or the traders. Farmers need higher price, which can be achieved, if more buyer across mandis participate. On the other side, the buyers i.e., traders of other mandis must get the guaranteed products for which they bid. For this, reliable assaying and storage are the thrust areas which cannot be ignored. It is expected that this model will lead to a new vista for logistics industry including both warehousing and transportation, thus creating a ripple effect in secondary agriculture.